Estimation of cerebrospinal fluid lactate level to differentiate between pyogenic and non-pyogenic meningitis: a prospective analytical study - Radhakrishna, Gurrala; Kumar, Anil; Krishna, Gurrala Kartheek (International Journal of Advances in Medicine, 2020)
Background: Meningitis is one of the common causes of serious morbidity and mortality and is one of the common causes of intensive care unit (ICU) admissions. The meningitis can be broadly divided into bacterial, viral or fungal meningitis. It is important to differentiate between pyogenic and non-pyogenic meningitis because of obvious management implications. Cerebrospinal fluid (CSF) lactate levels can be used for differentiating pyogenic and non-pyogenic (viral/tubercular) meningitis. Methods: This was a prospective analytical study in which cases diagnosed to be having meningitis were included on the basis of a predefined inclusion and exclusion criteria. Demographic details such as age, gender and socioeconomic status was note in all the cases. A detailed clinical history was taken and a through clinical examination was done. Imaging (computerized tomography) was done in selected cases. CSF cytology, biochemistry and culture sensitivity were done in all cases. CSF lactate was determined in all cases. Results: The CSF cytological examination showed that the mean total cell count was more (643.23±102.02) in pyogenic meningitis as compared to non-pyogenic (viral/tubercular) meningitis (121.76±59.74) and the difference was found to be statistically highly significant (p<0.0001). The analysis of CSF lactate levels showed that pyogenic meningitis cases had a significantly high level of CSF lactate as compared to non-pyogenic meningitis cases and the difference was found to be statistically highly significant (p<0.0001). Conclusions: CSF lactate level is a good indicator in differentiating pyogenic and non-pyogenic meningitis.